Normal Forms for Polynomial Differential Systems in R-3 Having an Invariant Quadric and a Darboux Invariant - Llibre, Jaume; Messias, Marcelo [UNESP]; Reinol, Alisson de Carvalho [UNESP] (World Scientific Publ Co Pte Ltd, 2015)
We give the normal forms of all polynomial differential systems in R-3 which have a nondegenerate or degenerate quadric as an invariant algebraic surface. We also characterize among these systems those which have a Darboux invariant constructed uniquely using the invariant quadric, giving explicitly their expressions. As an example, we apply the obtained results in the determination of the Darboux invariants for the Chen system with an invariant quadric.
Keywords: Polynomial differential systems; invariant quadric; Darboux integrability; Darboux invariant